The New Democratic Party and the Union Vote. - Dowler, Kevin John Gordon (University of Windsor, 2000)
The following study examines the NDP and the union vote. The NDP and labour unions have been officially linked since the NDP's formation in 1961. Despite the initial optimism of the NDP-labour link, the change from the CCF to the NDP has resulted in limited electoral success, especially at the federal level. The partnership between labour and the NDP has met with limited electoral fortunes. Although their tendency to vote NDP is higher than that of other groups, the vast majority of union members still vote for other parties. Federal election studies have repeatedly shown that 10 percent of non-union members, 20 percent of union members, and 30 percent of NDP affiliated union members vote for the NDP. The question is why do the remaining 70 to 80 percent of union members fail to vote for the NDP. This study aims to address this problem using survey research. The first chapter reviews the link between the NDP and labour and voting determinants in Canada. The second chapter looks at the research design and methodology of this thesis. Chapter three and four examines the results of the statistical analysis. Finally, chapter five summarizes with a discussion and concluding remarks.